1992
DOI: 10.1111/j.1365-2133.1992.tb00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Sweating response to moderate thermal stress in atopic dermatitis

Abstract: The local sweating response to thermal stress (mean ambient temperature 33 degrees C) was assessed under resting conditions on the non-eczematous back skin of 26 young men with atopic dermatitis (AD) and in 22 non-atopic controls with other dermatoses. The baseline (transepidermal) water loss was separately determined at room temperature (mean 23.6 degrees C) to calculate the pure sweat loss. A gravimetric collecting method was used for the measurements at 40, 60 and 80 min. In the heated room the sweat loss i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
0
17
0
4
Order By: Relevance
“…Healthy individuals perspired nearly three times as much as did patients with AD after induction through physical exercise (28). Accordingly, AD patients show significantly lower sweat rates upon moderate thermal stress (29). Differences in the composition of sweat, with reduced secretion of IgA (30) and altered sweat electrolyte concentrations (31) in children with AD, have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy individuals perspired nearly three times as much as did patients with AD after induction through physical exercise (28). Accordingly, AD patients show significantly lower sweat rates upon moderate thermal stress (29). Differences in the composition of sweat, with reduced secretion of IgA (30) and altered sweat electrolyte concentrations (31) in children with AD, have been described.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that NMF components which probably originate from sweat are significantly decreased in the SC of mild AD, suggesting that the sweat function is related to the development of SC dryness in AD. In fact, the sweat function in AD is decreased [35,36] and water loss due to sweating in a hot environment is decreased in AD patients because of the impaired response to environmental heat to stimulate sweating [35]. Moreover, it was reported that in diseased skin, such as AD, xerosis and psoriasis, sweat duct obstruction accompanying the hyperkeratosis also brings about the retention of sweat in the ducts which disturbs sweat delivery [37,38].…”
Section: Discussionmentioning
confidence: 97%
“…A variant of the method consists of collecting sweat on absorbent filter paper of defined dimensions placed in an occlusive device sealed airtight onto the skin [58]. The papers must be handled with forceps to avoid direct contact with the operator's fingers.…”
Section: Gravimetric Methodsmentioning
confidence: 99%